1990
DOI: 10.1037/0894-4105.4.1.29
|View full text |Cite
|
Sign up to set email alerts
|

The Capgras syndrome: Neurological/neuropsychological perspectives.

Abstract: The Capgras syndrome, as it is popularly known, is a colorful disorder in which the patient believes that a close friend, relative, etc., is not the "real"person but an exact look-alike, an impostor. Previous research has almost uniformly suggested that this syndrome is the result of long-standing intrapsychic conflicts, and thus a psychodynamic etiology was proffered. The focal point of this paper is to review the numerous references in the literature regarding a neurohgical/neuropsychological cause of the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 53 publications
1
5
0
Order By: Relevance
“…His neuropsychological profile is consistent with brain-imaging data: (i) dysexecutive and apatheticakinetic syndromes usually reflect bilateral frontal damage; (ii) retrograde episodic amnesia (Kopelman, 2002) presumably reflects the focal right temporal lesion (Markowitsch, 2003). These neuro-imaging findings are consistent with those described in other cases of misidentification syndrome, which showed bilateral frontal and right temporo-parietal hemisphere damage (Doran, 1990;Luzzatti & Verga, 1996;Devinsky, 2009). …”
supporting
confidence: 73%
See 1 more Smart Citation
“…His neuropsychological profile is consistent with brain-imaging data: (i) dysexecutive and apatheticakinetic syndromes usually reflect bilateral frontal damage; (ii) retrograde episodic amnesia (Kopelman, 2002) presumably reflects the focal right temporal lesion (Markowitsch, 2003). These neuro-imaging findings are consistent with those described in other cases of misidentification syndrome, which showed bilateral frontal and right temporo-parietal hemisphere damage (Doran, 1990;Luzzatti & Verga, 1996;Devinsky, 2009). …”
supporting
confidence: 73%
“…The DMS are considered pathological conditions of decreased (or increased) familiarity (Devinsky, 2009). Several neurological patients with delusions described in the literature presented bilateral frontal and right temporo-parietal lesions (Devinsky, 2009;Doran, 1990;Luzzatti & Verga, 1996). It has been suggested that right temporal lesions impair familiarity processing, causing familiar people, places, and body parts to appear foreign, and that the bilateral frontal dysfunction impairs the ability to monitor the appropriateness of the sense of familiarity emerging from the familiarity processing.…”
mentioning
confidence: 97%
“…In more recent studies, the delusion has served as the focus for an etiological debate supported by investigators who believe that the disorder has organic causes (Christodoulou, 1977;Collins et al, 1990;F6rstl, 1990;Joseph, 1986aJoseph, , 1986bJoseph et al, 1990;Luaut6 et al, 1990;Spier, 1992) and by investigators who are convinced that it is caused by psychodynamic factors (Berson, 1983;Christodoulou, 1977;Enoch and Trethowan, 1991;Koritar and Steiner, 1988;O'Reilly and Malhotra, 1987;Shraberg and Weitzel, 1979;Sinkman, 1983;Spier, 1992). McAllister (1992), Critchley (1989), Cutting (1991), Doran (1990), F6rstl (1990), and Koritar and Steiner (1988) have suggested that Capgras delusion stems from a coalescence of organic and psychodynamic factors. Signer (1992) reported that one-third of 488 cases of this so-called rare disorder and its variants showed a neurologic tendency.…”
Section: Capgras Delusionmentioning
confidence: 99%
“…The original Ellis and Young hypothesis included all sense modalities , but the fact they specifically used the visual processing of the face to argue their case appears to have led to a split in the literature. Some researchers predominately define the Capgras delusion as being specific to people (Bourget & Whitehurst: 2004;Brighetti et al 2007;Coltheart: 2007;Dietl, Brunner & Friess: 2003;Doran: 1990;Josephs: 2007;Tamam et al: 2003;Young, G. : 2008), whilst others extend the syndrome to include inanimate objects such as household furniture (Ellis et al: 1996;Nejad & Toofani: 2006) and animals, particularly pets ( Ellis et al: 1996;Rosler et al: 2001).…”
Section: Capgras For Inanimate Objectsmentioning
confidence: 99%